Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Pada PT Bank Negara Indonesia KCP Pamulang Tangerang Selatan - Angga Pratama (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2020)
The purpose of this study was to determine how the organizational culture of PT Bank Negara Indonesia KCP Pamulang Tangerang Selatan, find out how the performance of employees at PT Bank Negara Indonesia KCP Pamulang South Tangerang and determine the influence of organizational culture on employee performance, at PT Bank Negara Indonesia KCP Pamulang Tangerang Selatan. This type of research is associative descriptive research. The population and sample are all employees of PT Bank Negara Indonesia KCP Pamulang, South Tangerang. In this study carried out using the help of SPSS program ver. 23 that includes data quality tests, simple linear regression tests, correlation coefficient tests, hypothesis testing and coefficient of determination tests. The results of this study indicate that the organizational culture at PT Bank Negara Indonesia KCP Pamulang South Tangerang is already good, with answers from all respondents totaling 50 employees with